Is Sexual Harassment An Issue In Malaysia? Level of Awareness among Workforce - S. Baqutayan, Shadiya Mohamed; Salah, Amir; Jusman, Juliah; Sharudin, Shazila; Muhamad, Sunita; Saleh, Ahmed (Journal of Techno-Social, 2021)
The world has accomplished advancement in health workforce and wellbeing under the Sustainable Development Goals (SDGs); the goal comprises a healthy working environment and covering issues of harassment under human rights legislation. Nevertheless, the employees continue to suffer harassment in every part of the world. The SDGs’ objective is to ensure that there is an end to every issue. Undeniably, many governments and organizations claim to be tackling workplace harassment, and there are still a few billion employees who are the victims of harassment. This issue will not be solved unless awareness is given and policies introduced; therefore, the purpose of this paper is to investigate the level of awareness in the Malaysian government and private organizations. A research instrument, namely, a questionnaire, was used for 150 respondents and yielded a response rate of 52% (78). The results revealed that the work environment is concerned about safety matters for the workforce and has an adequate level of awareness on sexual harassment; therefore, the correlation tests revealed a significant correlation between workplace environment and awareness of sexual harassment among Malaysian staff. In conclusion, the organization should enforce the policy to establish a more conducive workplace favorable to the employees.